Young Children's Voices about their Local Communities. Issue 3 (September 2013) - Harris, Pauline; Manatakis, Harry
THREE HUNDRED AND FIFTY children were recently involved in statewide consultations to help inform the state government's review of its State Strategic Plan. This government wished to ensure children's views of their local communities were canvassed and their voices heard. These consultations were more than a tokenistic gesture—careful planning, implementation and documentation were carried out to ensure children's meaningful and sustained engagement over time. This article shares what children said—'said', that is—through the many voices children have to express their meaning through art, dance, music, song, drama, storytelling, photography, as well as oral and written language. This is their story. In 2009, the Council of Australian Governments launched its National Early Childhood Development Strategy, framed by a vision that 'all children have the best start in life to create a better future for themselves and for the nation' (COAG, 2009, p. 13). Underscoring this vision is the simple but highly significant recognition that:… [c]hildren are important. They bring their own value and influence to the world, as well as being shaped by the world around them … Children are also important for their future contribution to society, as the next generation of leaders, workers, parents, consumers and members of communities … in a global society (COAG, 2009, p. 7). Framed by a similar vision, the South Australia government's review of its State Strategic Plan in late 2010 involved consultations with communities. These consultations included children across the state under the ages of 12, with specific focus on children under the age of five to ensure their voices were heard. This paper reports on these consultations with young children aged between three and eight years, describing how the consultations were planned and implemented, and children's themes that emerged in relation to children's views of their local communities.